Increased Expression of Phosphorylated FADD in Anaplastic Large Cell and Other T-Cell Lymphomas. Issue 9 (January 2014) - Patel, Suketu; Murphy, Derek; Haralambieva, Eugenia; Abdulla, Zainalabideen A.; Wong, Kah Keng; Chen, Hong; Gould, Edith; Roncador, Giovanna; Hatton, Chris S.R; Anderson, Amanda P.; Banham, Alison H.; Pulford, Karen
FAS-associated protein with death domain (FADD) is a major adaptor protein involved in extrinsic apoptosis, embryogenesis, and lymphocyte homeostasis. Although abnormalities of the FADD/death receptor apoptotic pathways have been established in tumorigenesis, fewer studies have analyzed the expression and role of phosphorylated FADD (pFADD). Our identification of FADD as a lymphoma-associated autoantigen in T-cell lymphoma patients raises the possibility that pFADD, with its correlation with cell cycle, may possess role(s) in human T-cell lymphoma development. This immunohistochemical study investigated pFADD protein expression in a range of normal tissues and lymphomas, particularly T-cell lymphomas that require improved therapies. Whereas pFADD was expressed only in scattered normal T cells, it was detected at high levels in T-cell lymphomas (eg, 84% anaplastic large cell lymphoma and 65% peripheral T cell lymphomas, not otherwise specified). The increased expression of pFADD supports further study of its clinical relevance and role in lymphomagenesis, highlighting phosphorylation of FADD as a potential therapeutic target.